DIVERSITY AND CATCHING STATUS OF GROUPER (SERRANIDAE) IN COASTAL WATERS OF DA NANG AND QUANG NAM - Quang, Vo Van; Thao, Le Thi Thu; Vi, Nguyen Thi Tuong; Hoa, Tran Thi Hong; Vu, Nguyen Phi Uy; Thinh, Tran Cong (Vietnam Journal of Marine Science and Technology, 2016)
The serranid species composition of the family Serranidae recorded in coastal areas of Da Nang and Quang Nam was diverse with 30 species of six genera (21 species recorded in Da Nang and 25 species found in Quang Nam), which occupies 60% of the grouper species known from the coral reef of Vietnam (50 species), 42% of the recognized species from Vietnam’s sea waters (72 species) and 24% of recognized grouper species from the East Vietnam Sea (126 species). Additionally, the genus Epinephelus is the most diverse with 17 species. The groupers recorded from Da Nang and Quang Nam waters are more diverse compared with those from northern waters, such as Quang Ninh and coastal zone of North Central area. The serranid species (groupers) recorded in coastal areas of Da Nang and Quang Nam have a high similarity with those in regions in the north, such as Quang Ninh, coastal waters of the North Central coastal zone, Hong Kong. However, they have lower levels of homology with those in regions in the south, including the reef of South Central coastal zone, coral reef in Truong Sa archipelago, coral reefs of Vietnam and they have the lowest level of homology with those in Taiwan. The serranid species commonly caught in Da Nang and Quang Nam are Chocolate Hind (Cephalopholis boenak) 43%, Yellow grouper (E. awoara) 18% and Black-dotted grouper (E. stictus) 16%. The length of groupers caught is generally targeted in small species and juveniles (unmatured size) of large species as Yellow grouper (Epinephelus awoara), Duskytail grouper (E. bleekeri), Orange-spotted grouper (E. coioides), Malabar grouper (E. malabaricus) and Longtooth grouper (E. bruneus).